Solve for y t=x-2y

Math
t=x-2y
Rewrite the equation as x-2y=t.
x-2y=t
Subtract x from both sides of the equation.
-2y=t-x
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=t-x by -2.
-2y-2=t-2+-x-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=t-2+-x-2
Divide y by 1.
y=t-2+-x-2
y=t-2+-x-2
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
y=-t2+-x-2
Dividing two negative values results in a positive value.
y=-t2+x2
y=-t2+x2
y=-t2+x2
Solve for y t=x-2y

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top